An alternative sigma factor governs the principal sigma factor in Streptomyces griseus. Issue 6 (21st February 2013) - Otani, Hiroshi; Higo, Akiyoshi; Nanamiya, Hideaki; Horinouchi, Sueharu; Ohnishi, Yasuo
Summary In bacteria, the RNA polymerase holoenzyme comprises a five‐subunit core enzyme and a dissociable subunit, sigma factor, which is responsible for transcriptional initiation. The filamentous bacterium Streptomyces griseus has 52 sigma factors, including one essential 'principal' sigma factor (σHrdB) that is responsible for the transcription of housekeeping genes. Here we characterized an alternative sigma factor (σShbA), which is highly conserved within the genus Streptomyces. A σShbA‐deficient mutant showed a severe growth defect and transcriptome analysis indicated that many housekeeping genes were downregulated in response to insufficient σShbA production. Biochemical and genetic analyses proved that σShbA is a major determinant of transcription of the σHrdB gene. This observation of a principal sigma factor being governed by another sigma factor throughout growth is unprecedented. We found that increasing σShbA production with mycelial growth maintained a high σHrdB level late in growth. Furthermore, a hrdB‐autoregulatable σShbA‐deficient mutant, in which the principal sigma factor gene can be transcribed by RNA polymerase containing σHrdB itself, showed several defects: rapid mycelial lysis in stationary phase in liquid culture and delayed morphological development and impaired streptomycin production in solid culture. From these observations, we discuss the biological significance of control of σHrdB by σShbA in S. griseus.